PENGARUH KEPEMIMPINAN, PENGEMBANGAN KARIR DAN HUMAN RELATION TERHADAP KINERJA KARYAWAN PADA KANTOR OTORITAS BANDAR UDARA WILAYAH II KUALANAMU - Simanjuntak, Hotman Saniapoh; Sitanggang, Darna; Sihombing, Sarimonang; Manullang, Ida M (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The aim of this research is to find out and explain Leadership, Career Development and Human Relations on Employee Performance at the Kualanamu Region II Airport Authority Office. namely in the form of a statement that is accompanied by previous alternative answers, so that respondents can choose one of the alternatives. The techniques used in this research include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing (F test and t test) and coefficient of determination analysis. Data analysis in this research uses SPSS version 25. From the research results This shows that the multiple linear regression equation where: Y = 1,218+ 0,310X1 + 0,425X2 + 0,224X3 Leadership, Career Development, and Human Relations variables together (simultaneously) have a positive and significant effect on employee performance at the Kualanamu Region II Airport Authority Office. While partially showing that leadership has a positive and significant effect on employee performance at the Kualanamu Region II Airport Authority Office with a multiple regression coefficient value of 0.310 and a significant value of 0.003 <0.05 (smaller than the error tolerance value), career development has a positive and significant effect on employee performance at the Kualanamu Region II Airport Authority Office with a multiple regression coefficient value of 0. 425 and a significant value of 0.000 <0.05 (smaller than the error tolerance value), 425 and a significant value of 0.000 <0.05 (smaller than the error tolerance value), human relations have a positive and significant effect on employee performance at the Kualanamu Region II Airport Authority Office with a multiple regression coefficient value of 0.224 and a significant value of 0.007 <0.05 (smaller than the error tolerance value).